Bayesian Mapping for Infectious Bronchitis Virus Risk in Backyard Chickens in Paraguay - Origlia, J.; Suzuki, K.; Castro, L.; Faccioli, M.; Silva, M.; Caballero, J.; Valiente, O.; Alvarez, F. (International Journal of Poultry Science, 2009)
Poultry production is a developing industry in Paraguay, South America. The inadequate farm management methods commonly used in backyard chickens make them a potential reservoir for economically important diseases such as infectious bronchitis that can affect commercial poultry operations. There are no earlier studies on a survey of Infectious Bronchitis Virus (IBV) amongst backyard chicken population in Paraguay. The objectives of this study were: (1) to observe the seroprevalence of IBV in backyard chickens in Paraguay and (2) to generate maps for estimated seroprevalence using Bayesian techniques for IBV in the study chickens and for smoothed Relative Risks (RR) drawn by one of the techniques above, in place of using the observed seroprevalence. Paraguay consists of 17 departments. A department-stratified random sampling was designed and implemented. The required total sample size of 1537 from a chicken population of 17 million was adequate to produce a 95% confidence interval with a desired precision of ±2.5% when the estimated seroprevalence was 50%. Sera were analyzed using a commercial indirect ELISA. The overall observed antibody seroprevalence was 80%. The resulting maps for the estimated seroprevalence for IBV using Bayesian techniques in the study chickens at department level, and for the smoothed RRs were illustrated. Different types of epidemiological parameters can be computed to take account of potential risk factors. Therefore, further detailed studies into those risk factors associated with IBV appearance with respect to spatially epidemiological variations would be of interest.